Governance in contemporary Germany the semisovereign state revisited - Green, Simon 1971-; Paterson, William E. 1941- (Cambridge University Press, 2005)
Throughout the 1970s and 1980s, West Germany was considered to be one of the world's most successful economic and political systems. In his seminal 1987 analysis of West Germany's 'semisovereign' system of governance, Peter Katzenstein attributed this success to a combination of a fragmented polity, consensus politics and incremental policy changes. However, unification in 1990 has both changed Germany's institutional configuration and created economic and social challenges on a huge scale. This 2005 volume therefore asks whether semisovereignty still exists in contemporary Germany and, crucially, whether it remains an asset in terms of addressing these challenges. By shadowing and building on the original study, an eminent team of British, German and American scholars analyses institutional changes and the resulting policy developments in key sectors, with Peter Katzenstein himself providing the conclusion. Together, the chapters provide a landmark assessment of the outcomes produced by one of the world's most important countries
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Geschichte 1990-2005; Geschichte; Politik; Politisches System; Deutschland; Germany / Politics and government / 1990-; Germany / History / Unification, 1990; Aufsatzsammlung